SURVEY ON NUTRITIONAL STATUS AND BODY MASS INDEX ATHLETES IN Wrestling Sports Branch in Preparation for PORDA DIY 2022 - Ardini Dwi Meiwati; Ardhika Falaahudin (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
Sports coaching and development is an effort to improve the quality of human beings in Indonesia which is directed at improving the physical, mental and spiritual health of the community and is shown to form the character and personality of discipline and high sportsmanship. Wrestling is a sport that has long been known to humans, the origins of wrestling can be traced back 15,000 years ago through historical data. This study aims to determine the nutritional status and body mass index of athletes in the Wrestling sport in preparation for PORDA DIY 2022 and the level of food consumed. The research method used is descriptive quantitative. The sample in this study were Porda athletes in the Bantul district wrestling contingent. The results of this study note that the nutritional status of athletes in the sport of wrestling in preparation for PORDA DIY 2022 is mostly sufficient. In addition, it is also known that the majority of respondents have a normal body mass index and 1 respondent is obese. Respondents always count every nutrient consumed in order to maintain nutritional adequacy.